Analisis Efisiensi Pemasaran Sapi Potong di Kecamatan Teon Nila Serua Kabupaten Maluku Tengah - Matatula, M J; Rajab, Rajab; Kewilaa, A I (Politeknik Negeri Lampung, 2025)
This study aims to analyze marketing channels, marketing margins and the level of beef cattle marketing efficiency in Teon Nila Serua District, Central Maluku Regency. The research method used is a survey method. Determination of samples by purposive sampling for farmers and traders. The number of samples was 36 respondents consisting of 25 farmers and 11 traders. The variables observed were: marketing channels, marketing margins and marketing efficiency. The data analysis method used was descriptive analysis to determine the marketing channels, marketing margin analysis and